Synergistic Utility of Brain Natriuretic Peptide and Left Ventricular Strain in Patients With Significant Aortic Stenosis. Issue 1 (5th January 2016) - Goodman, Andrew; Kusunose, Kenya; Popovic, Zoran B.; Parikh, Roosha; Barr, Tyler; Sabik, Joseph F.; Rodriguez, L. Leonardo; Svensson, Lars G.; Griffin, Brian P.; Desai, Milind Y.
Abstract : Background: In aortic stenosis (AS), symptoms and left ventricular (LV) dysfunction represent a later disease state, and objective parameters that identify incipient LV dysfunction are needed. We sought to determine prognostic utility of brain natriuretic peptide (BNP) and left ventricular global longitudinal strain (LV‐GLS) in patients with aortic valve area <1.3 cm 2 . Methods and Results: Five‐hundred and thirty‐one patients between January 2007 and December 2008 with aortic valve area <1.3 cm 2 (86% with aortic valve area ≤1.1 cm 2 ) and left ventricular ejection fraction ≥50% who had BNP drawn ≤90 days from initial echo were included. Society of Thoracic Surgeons (STS) score and mortality were recorded. Mean STS score, glomerular filtration rate, and median BNP were 11±5, 73±35 mL/min per 1.73 m, and 141 (60–313) pg/mL, respectively; 78% were in New York Heart Association class ≥II. Mean LV‐stroke volume index (LV‐SVI) and LV‐GLS were 39±10 mL/m 2 and −13.9±3%. At 4.7±2 years, 405 patients (76%) underwent aortic valve replacement; 161 died (30%). On multivariable survival analysis, age (hazard ratio [HR] 1.46), New York Heart Association class (HR 1.27), coronary artery disease (HR 1.72), decreasing glomerular filtration rate (HR 1.15), increasing BNP (HR 1.16), worsening LV‐GLS (HR 1.13) and aortic valve replacement (time dependent) (HR 0.34) predicted survival (all P <0.01). For mortality, the c‐statistic incrementally increased as follows (all P <0.01): STS score (0.60 [0.58–0.64]), STS score+BNP (0.67 [0.62–0.70]), and STS score+BNP+LV‐GLS (0.74 [0.68–0.78]). Conclusions: In normal LVEF patients with significant aortic stenosis, BNP and LV‐GLS provide incremental (additive not duplicative) prognostic information over established predictors, suggesting that both play a synergistic role in defining outcomes.